'Tricks' for revealing potential attentional modulations on the C1 component. Issue 1 (3rd April 2018) - Fu, Shimin
ABSTRACT: The t-test formula for a within-subject design suggests that the C1 attentional effect is more likely to be significant if the C1 attentional difference, as the numerator, is large and the standard deviation of the C1 difference that affects the denominator is small. Experimental manipulations for exploring potential C1 attentional effects can be evaluated by their contributions to the numerator and/or the denominator of the t-test formula. 'Tricks' that may enhance the C1 attentional difference and minimize the standard deviation of the sampled C1 are discussed.